HIBAH IN TAKAFUL BENEFIT: ISSUES AND SOLUTIONS - Megat Laksana, Nan Noorhidayu; Abdullah, Nurdianawati Irwani; Abdul Aziz, Akhtarzaitie (2017)
This paper examined the validity of executing hibah in Participant Investment Fund (PIF), upon occulrence of certain event such as participant's death, whether it should take effect after participant dies or during the lifetime of the participant. This paper will also conduct an empirical study related to the issues in order to examine the theoretical aspects relevant to the practice of mkaful industry. Besides, this study only focuses on the family takdful plut because it is related to death. For this research, the researcher adopted semi-structured interviews because this type of interview is able to collect both qualitative and quantitative data. The researcher has conducted interview session with I 7 Shar|'ah advisors, ll SharT'ah officers and 3 takaful experts at eleven talatful operators in Malaysia. With regards to the issue of hibah, all takaful operators in Malaysia already applied hibah distribution and a nominee can be considered either as an executor or a beneficiary in nomination. Even though there are some Shart'aft scholars disagreed with the implementation of hibah ruqba, the researcher found that hibah ruqba is relevant to be applied in nomination. In addition, the main contribution of this study is, to facilitate or monitor the application of hibah ruqba by all mkaful operators in Malaysia.